Intracellular calcium buffering capacity in isolated squid axons - Brinley, FJ (The Rockefeller University Press, 1977)
Changes in ionized calcium were studied in axons isolated from living squid by measuring absorbance of the Ca binding dye Arsenazo III using multiwavelength differential absorption spectroscopy. Absorption changes measured in situ were calibrated in vitro with media of ionic composition similar to axoplasm containing CaEGTA buffers. Calcium loads of 50-2,500 μmol/kg axoplasm were induced by microinjection, by stimulation in 112 mM Ca seawater, or by soaking in choline saline with 1-10 mM Ca. Over this range of calcium loading of intact axoplasm, the ionized calcium in the axoplasm rose about 0.6 nM/μM load. Similar loading in axons preteated with carbonyl cyanide 4- trifluoromethoxyphenylhydrazone (FCCP) to inhibit the mitochondrial proton gradient increased ionized calcium by 5-7 percent of the imposed load, i.e. 93-95 percent of the calcium load was buffered by a process insensitive to FCCP. This FCCP- insensitive buffer system was not saturated by the largest calcium loads imposed, indicating a capacity of at least several millimolar. Treatment of previously loaded axons with FCCP or apyrase plus cyanide produced rises in ionized calcium which could be correlated with the extent of the load. Analysis of results indicated that, whereas only 6 percent of the endogenous calcium in fresh axons is stored in the FCCP-sensitive (presumably mitochondrial) buffer system, about 30 percent of an imposed exogenous load in the range of 50-2,500 μM is taken up by this system.